Improving Student Learning Outcomes of Class VIII.3 SMP Negeri 16 Kendari on the Area of a Circle through the Use of Props - Nurmin (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This class action research was conducted based on the learning outcomes of students of class VIII.3 SMP Negeri 16 Kendari, who were very low in determining the area of ​​a circle. One of the efforts to improve student learning outcomes is by using teaching aids in the teaching and learning process of mathematics. The objectives of this classroom action research are: (a) to improve the professionalism of teachers in the learning process in the classroom when the teacher teaches the area of ​​a circle using visual aids, and (b) to improve the learning outcomes of class VIII.3 students of SMP Negeri 16 Kendari in the area of ​​a circle through use of props. The subjects of this study were students of class VIII.3 SMP Negeri 16 Kendari opened 30 students. This classroom action research was designed for two cycles. Each cycle has stages: planning, implementation, observation, and reflection. The study results in the first cycle of 30 students subjected to action; only 14 students (46.7%) who completed their learning outcomes experienced an increase in the second cycle of 24 students (80.0%). The results showed increased student learning outcomes in class VIII—3 SMP Negeri 16 Kendari in the area of ​​a circle through the use of teaching aids.